Visual aesthetic dan storytelling meningkatkan impulsive buying di media sosial - Imanuella Gracia Maharani; Kezia Kurniawati Nursalin (Vikara: Student Academic Journal of Business and Management, 2026)
The development of social media has driven changes in digital marketing strategies, particularly through visual and narrative elements. This study aims to analyze the influence of visual aesthetic and storytelling on impulsive buying among active Instagram and TikTok users, particularly among students at Maranatha Christian University. This research was conducted using a quantitative approach and multiple regression analysis. The sampling technique used was purposive sampling, with 175 respondents. The results showed that partially, visual aesthetics had no significant effect on impulsive buying, while storytelling had a significant effect. Simultaneously, visual aesthetics and storytelling together had a significant effect on impulsive buying. These findings emphasize the importance of storytelling as a key element in triggering impulsive buying decisions on digital platforms, rather than relying solely on visual appeal. This research provides practical implications for businesses and content creators in designing strong narrative-based digital marketing strategies that engage audiences emotionally.